2022
DOI: 10.3390/medicina58010090
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Therapy for Non-Muscle-Invasive Bladder Cancer: What Is the Real Impact of Squamous Cell Carcinoma Variant on Oncological Outcomes?

Abstract: Background and Objectives: To evaluate the oncological impact of squamous cell carcinoma (SCC) variant in patients submitted to intravesical therapy for non-muscle-invasive bladder cancer (NMIBC). Materials and Methods: Between January 2015 and January 2020, patients with conventional urothelial NMIBC (TCC) or urothelial NMIBC with SCC variant (TCC + SCC) and submitted to adjuvant intravesical therapies were collected. Kaplan–Meier analyses targeted disease recurrence and progression. Uni- and multivariable Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The most predominant histological phenotype is TCC, which constitutes approximately 80% of BC. [17] Bladder SCC accounts for only 2 to 5% of BCs, but it has the characteristics of a high malignancy degree and a high recurrence rate, [18] and progresses faster than TCC in BC patients at stage III or IV. [19] In our study, we concluded that SCC was also associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The most predominant histological phenotype is TCC, which constitutes approximately 80% of BC. [17] Bladder SCC accounts for only 2 to 5% of BCs, but it has the characteristics of a high malignancy degree and a high recurrence rate, [18] and progresses faster than TCC in BC patients at stage III or IV. [19] In our study, we concluded that SCC was also associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%